Occurrence of an invasive coral in the southwest Atlantic and comparison with a congener suggest potential niche expansion. Issue 11 (6th May 2015) - Carlos‐Júnior, Lélis A.; Neves, Danilo M.; Barbosa, Newton P. U.; Moulton, Timothy P.; Creed, Joel C.
Abstract Tubastraea tagusensis, a coral native to the Galapagos Archipelago, has successfully established and invaded the Brazilian coast where it modifies native tropical rocky shore and coral reef communities. In order to understand the processes underlying the establishment of T. tagusensis, we tested whether Maxent, a tool for species distribution modeling, based on the native range of T. tagusensis correctly forecasted the invasion range of this species in Brazil. The Maxent algorithm was unable to predict the Brazilian coast as a suitable environment for the establishment of T. tagusensis. A comparison between these models and a principal component analysis (PCA) allowed us to examine the environmental dissimilarity between the two occupied regions (native and invaded) and to assess the species' occupied niche breadth. According to the PCA results, lower levels of chlorophyll‐a and nitrate on the Atlantic coast segregate the Brazilian and Galapagos environments, implying that T. tagusensis may have expanded its realized niche during the invasion process. We tested the possible realized niche expansion in T. tagusensis by assuming that Tubastraea spp. have similar fundamental niches, which was supported by exploring the environmental space of T. coccinea, a tropical‐cosmopolitan congener of T. tagusensis. We believe that the usage of Maxent should be treated with caution, especially when applied to biological invasion (or climate change) scenarios where the target species has a highly localized native (original) distribution, which may represent only a small portion of its fundamental niche, and therefore a violation of a SDM assumption.